The Career Goals of Female Science Students in Canada - Nevitte, N.; Gibbins, R.; Codding, P. W. (Canadian Journal of Higher Education, 1988)
There are relatively few women in the Canadian scientific community and most of the available research explains this fact in terms of girls' low enrolment in high school science programmes. The research presented here suggests that the substantial seepage of women from science at a later decision-point also contributes to the lack of women in the science professions. The career goals of a matched sample of male and female senior science undergraduates at nine Canadian universities (N = 204) are examined. The data show (1) that there are substantial gender discrepancies in the defection rates and career aspirations of male and female science undergraduates; (2) that fathers occupation emerges as a relevant background variable distinguishing female science students from their male counterparts; and (3) academic performance affects the defection rate of women from science-the top performers are more likely than average performers to defect from science. These findings are related to cross-national data and strategies for further research are suggested.